Morphology variation of Lutzomyia cruciata eggs (Diptera: Psychodidae: Phlebotominae) in southern Mexico - Oca-Aguilar, Ana Celia Montes De; Mikery-Pacheco, Oscar; Castillo, Alfredo; Rebollar-Téllez, Eduardo A.; Piermarini, Peter M.; Ibáñez-Bernal, Sergio (Zootaxa, 2017)
The sand fly Lutzomyia cruciata has been associated with the transmission of Leishmania mexicana to humans in Mexico. This species has a wide distribution in Mexico occupying different microhabitats and environments. In this work comparisons of the egg exochorion of Lu. cruciata from different physiographic areas are presented. Study sites are from different states of southern Mexico. Exochorion analysis was carried out using scanning electron microscopy (SEM). Results show differences in the exochorionic pattern among samples from Veracruz (AVER), Yucatán (HOYU) and Chiapas (TACH). The morphotype “Chiapas” has a polygonal crest pattern, the morphotype “Veracruz” shows parallel and longitudinal crests with some or few connections, and the morphotype “Yucatán” has weak connections between crest ridges. These morphological differences could be the result of local adaptations or evidence of divergence within the nominal unit Lutzomyia cruciata.